Fashioning America : Grit to Glamour - Finamore, Michelle Tolini (Book collections on Project MUSE., 2022)
"The companion volume to Crystal Bridges Museum of American Art's first fashion exhibition, Fashioning America: Grit to Glamour celebrates the history of American attire, from the cowboy boot to the zoot suit"--